Historik kirchlicher Zeitgeschichte und systematisch-theologische Urteilsbildung - Welker, Michael (Kirchliche Zeitgeschichte, 1992)
This article discusses the tasks and methodologies developed in the research of contemporary church historians, such as J. Mehlhausen, G. Besier, H. G. Ulrich and others, and seeks to show how these scholars have reacted to the new situation in which the former distinctions between 'Modern History' and 'Contemporary History before and after 1945' are presently being eliminated. New and more relativistic theories are obliging historians to engage in a much more pluralistic system of values and ideas, as can be seen in the work of Koselleck, Luhmann and others. The discussion centres around how to distinguish between general and particular themes in contemporary history, and this paper discusses the consequences for the methodology of contemporary historical research. We have to overcome the unfortunate alternative of vacillating between the 'old' totalized view of 'History' and a proliferation of 'contemporary profiles', which often leads to a reductionist view based on the existential position of each contemporary historian. What we need to find is methodologies and intellectual frameworks which can include theological components, and which can thus meet the new challanges presented by recent developments in critical scholarship.
Gesehen am 30.09.2024